Dynamic fiber-optic shape sensing using fiber segment interferometry - Kissinger, Thomas; Chehura, Edmond; Staines, Stephen E.; James, Stephen W.; Tatam, Ralph P. (IEEE, 2017)
Dynamic fiber-optic shape sensing, often also referred to as curvature or bend sensing, is demonstrated using fiber segment interferometry, where chains of fiber segments, separated by broadband Bragg grating reflectors, are interrogated using range-resolved interferometry. In this work, the theory of interferometric curvature sensing using fiber segments is developed in detail, including techniques to infer lateral displacements from the measured differential strain data and methods for directional calibration of the sensor. A proof-of-concept experiment is performed, where four fiber strings, each containing four fiber segments of gauge length 20 cm each, are attached to the opposing sides of a flexible support structure and the resulting differential strain measurements are used to determine the lateral displacements of a 0.8 m cantilever test object in two dimensions. Dynamic tip displacement measurements at 40nm . HZ-0.5 noise levels over a 21 kHz bandwidth demonstrate the suitability of this approach for highly sensitive and cost-effective fiber-optic lateral displacement or vibration measurements.
Keywords: Optical fiber sensors; Optical interferometry; Vibrometers; Shape measurement; Condition monitoring